The risk-relevance of securitizations during the recent financial crisis - DOU, Yiwei (Institutional Knowledge at Singapore Management University, 2014)
We investigate changes in the risk-relevance of securitized subprime, other nonconforming, and commercial mortgages for sponsor-originators during the recent financial crisis. Using the volatility of realized stock returns, option-implied volatility, and credit spreads, we observe a pronounced increase in the risk-relevance of subprime securitizations as early as 2006. Furthermore, reflecting the evolution of the financial crisis in waves, we find that investors recognized the increased credit risk of other nonconforming and commercial mortgage securitizations as the financial crisis progressed. Additional analyses show that risk-relevance varies cross-sectionally with structural characteristics such as monoline credit-enhancement and the presence of special servicers for commercial mortgage securitizations. Our results inform the current debates on the opacity of securitization structures and highlight the need to take into account cross-sectional and inter-temporal heterogeneity in risk-relevance across securitized asset classes and securitization characteristics (e.g., quality and type of collateral and transaction structure).